Analisis Pengaruh Pembiayaan Murabahah, Mudharabah, dan Musyarakah Terhadap Profitabilitas Bank Syariah (periiode Desember 2007-Desember 2014) - Susanto, Agus; , Eni Setyowati, SE, M.Si; , Dr. Imron Rosyadi M.Ag (2016)
This study aims to determine the effect of Financing Murabaha, Mudaraba and Musharaka to Profitability Muamalah Bank Indonesia (BMI) and Bank Syariah Mandiri ( BSM ) in the period from December 2007 to December 2014. The method used is Rigres Multiple Ordinary, who observed the level of profitability generated of the independent variable. The results of this testing are expected to be used as a performance improvement of Islamic banking in particular BMI and BSM to better get a higher profit.The results in this experiment showed that only Musharaka financing in BMI had no significant effect, while the Murabahah and Mudharabah financing significant effect on BMI. Sedangka financing Murabaha, Mudaraba and Musharaka significant effect on the profitability of BSM.